2019
DOI: 10.1140/epjc/s10052-019-7331-1
|View full text |Cite
|
Sign up to set email alerts
|

Contraction of cold neutron star due to in the presence a quark core

Abstract: Motivated by importance of the existence of quark matter on structure of neutron star. For this purpose, we use a suitable equation of state (EoS) which include three different parts: (i) a layer of hadronic matter, (ii) a mixed phase of quarks and hadrons, and, (iii) a strange quark matter in the core. For this system, in order to do more investigation of the EoS, we evaluate energy, Le Chatelier's principle and stability conditions. Our results show that the EoS satisfies these conditions. Considering this E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…This holds for several EoS that satisfy current observational and particle physics constraints, computed according to various techniques and with different particle contents. This approximation also holds for EoS describing strange quark stars (see [71] for an account of the deformation of a NS due to the presence of a quark core), although with a smaller accuracy. On the other hand, it was previously found [62] that the GR moment of inertia I is also well approximated, for a large sample of EoS, by a function of just the mass and radius of the NS.…”
Section: Methodsmentioning
confidence: 96%
“…This holds for several EoS that satisfy current observational and particle physics constraints, computed according to various techniques and with different particle contents. This approximation also holds for EoS describing strange quark stars (see [71] for an account of the deformation of a NS due to the presence of a quark core), although with a smaller accuracy. On the other hand, it was previously found [62] that the GR moment of inertia I is also well approximated, for a large sample of EoS, by a function of just the mass and radius of the NS.…”
Section: Methodsmentioning
confidence: 96%
“…The present study is also relevant for the possible implications to understand the nature of compact stars. Recently, a few authors suggested that strange matter could exist in the core of NS-hybrid stars [22][23][24], while others claim such stars are almost indistinguishable from NS [25]. In addition to that, strange quark stars may explain some puzzling super-luminous supernovae [26,27], which occur in about one out of every 1000 supernovae explosions, and which are more than 100 times more luminous than regular supernovae.…”
Section: Introductionmentioning
confidence: 99%
“…The core of dense stars, pulsars, neutron stars, and the presence of strange quark stars support the existence of SQM. [ 4–7 ] The study of SQM with quasi particle is one of the most interesting area of research. The masses of quarks vary with environment and it is suggested to be the function of density, momentum incorporating medium effect in the context of fermi model.…”
Section: Introductionmentioning
confidence: 99%